2018
DOI: 10.1186/s12879-018-3023-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and mortality rates of varicella among end stage renal disease (ESRD) patients in Singapore General Hospital, a 12-year review

Abstract: BackgroundEnd stage renal disease (ESRD)/ end stage renal failure (ESRF) is on the rise globally and especially in Singapore. Varicella or chickenpox is not uncommon among adults especially ESRD/ESRF patients. It has been reported to cause complications and even death among immunocompetent adults.MethodsA retrospective data collection on patients with varicella infection and ESRD in Singapore General Hospital (SGH) from the year 2005 to 2016 was performed. Continuous data and categorical data were summarized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Out of the seven studies on the prevalence of seronegative results; four studies were on the prevalence of seronegativity among ESRD patients upon presentation of the varicella disease [ 9 , 13 15 ]. The results showed that 42 to 100% of the patients who contracted varicella had no prior immunity to varicella.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Out of the seven studies on the prevalence of seronegative results; four studies were on the prevalence of seronegativity among ESRD patients upon presentation of the varicella disease [ 9 , 13 15 ]. The results showed that 42 to 100% of the patients who contracted varicella had no prior immunity to varicella.…”
Section: Resultsmentioning
confidence: 99%
“…In this review, the prevalence of seronegativity among varicella-infected ESRD adults was found to be significantly alarming at 42 to 100% [ 9 , 13 15 ]. Nineteen deaths were reported in 23 studies that reported the varicella infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Varicella-Zoster virus (VZV) is epitheliotropic and neurotropic, but it is also possible to generalize the process with damage to the internal organs: liver, lungs, and gastrointestinal tract [12][13][14]. The most important risk factors associated with the severity of varicella, generalization of the process and death are age and impaired function of the immune system [15][16][17].…”
Section: Introductionmentioning
confidence: 99%